2022
DOI: 10.21608/ejhm.2022.266042
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Immunoglobulin G and Gender between COVID-19 Patients and Vaccinated Iraqi Individuals with Pfizer, AstraZeneca and Sinopharm Vaccine

Abstract: Background: The coronavirus 2 that causes severe acute respiratory syndrome is the source of the contagious sickness known as coronavirus disease 2019, The first case was detected in Wuhan, China, in December of this year. Since then, a pandemic has occurred due to the disease's global spread. The IgG antibody is a large, Y-shaped protein that aids in the immune system's ability to identify and eliminate foreign substances like bacteria and viruses. The antibody detects the antigen, a distinct molecular molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, this study demonstrated that the Oxford-AstraZeneca had more effective in raising IgG in seropositive subjects than the Sinopharm. 52 This phenomenon may be correlated to hybrid immunity. It is suggested that antibodies produced by previous SARS-CoV-2 infection combine with post-vaccination antibodies to develop “hybrid immunity.” 53 , 54 Thus, combination of acquired natural immunity to SARS-CoV-2 with vaccine-generated protection can provide a larger-than-expected immunological response.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study demonstrated that the Oxford-AstraZeneca had more effective in raising IgG in seropositive subjects than the Sinopharm. 52 This phenomenon may be correlated to hybrid immunity. It is suggested that antibodies produced by previous SARS-CoV-2 infection combine with post-vaccination antibodies to develop “hybrid immunity.” 53 , 54 Thus, combination of acquired natural immunity to SARS-CoV-2 with vaccine-generated protection can provide a larger-than-expected immunological response.…”
Section: Discussionmentioning
confidence: 99%